Analysis of the influence of the competition rules in excellence and aesthetics expression of the artistic gymnastics performance - Corte-Real, A.; Lacerda, T.; Carvalho, J. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Artistic Gymnastics (AG) is increasing nowadays due to ethic and aesthetic performance of gymnasts which contribute to the high quality of sports exhibition. Throughout its history and development it`s possible to find spectacularity as result of the work made by gymnasts in the present and future. Spectacularity in AG can be seen as a show as well as in most of the others sports and it has been increasing in the last decades. Constantino (1990) says that (...) sports are becoming one of the greatest world theatre, with a powerful visual impact " (p 81,82). This study pretended to analyse the influence of competitions rules on spectacularity and understand how it is seen by different individuals. We compare common observers (public in general) and specialize observers (public related to gymnastics). Methods The sample consisted of two different groups of observers (n = 53), answering to series of two questions immediately after watching images of two exercises on balance beam. Although both exercises had a maximum start value, they showed, according to experts, different difficulty/spectacularity level. The questions were: which was the most spectacular exercise and which was the most difficult. Results/Conclusion The values found in the study showed a clear difference between the two groups of observers.